Broadly-Neutralizing Antibodies Against Emerging SARS-CoV-2 Variants - Shrestha, Lok Bahadur; Tedla, Nicodemus; Bull, Rowena A. (Frontiers in Immunology, 2021)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants have become a major concern in the containment of current pandemic. The variants, including B.1.1.7 (Alpha), B.1.351 (Beta), P1 (Gamma) and B.1.617.2 (Delta) have shown reduced sensitivity to monoclonal antibodies, plasma and/or sera obtained from convalescent patients and vaccinated individuals. Development of potent therapeutic monoclonal antibodies (mAbs) with broad neutralizing breadth have become a priority for alleviating the devastating effects of this pandemic. Here, we review some of the most promising broadly neutralizing antibodies obtained from plasma of patients that recovered from early variants of SARS-CoV-2 that may be effective against emerging new variants of the virus. This review summarizes several mAbs, that have been discovered to cross-neutralize across Sarbecoviruses and SARS-CoV-2 escape mutants. Understanding the characteristics that confer this broad and cross-neutralization functions of these mAbs would inform on the development of therapeutic antibodies and guide the discovery of second-generation vaccines.